Spatial effects of innovation ecosystem development on low-carbon transition - Bin Cao; Fanlin Meng; Bingjun Li (Ecological Indicators, 2023)
In the context of innovation-driven development, the effective transformation of the low-carbon economy increasingly relies on the innovation ecosystem in which it exists. In order to explore the spatial effect of the innovation ecosystem on low-carbon transformation, this study comprehensively measures the innovation ecosystem and low-carbon transformation level based on China’s provincial panel data from 2015 to 2020 and use the spatial Durbin model to analyze the impact of the innovation ecosystem on low-carbon transition. The main conclusions are as follows: (1) There is apparent spatial heterogeneity in the development of innovation ecosystems, and the development pattern shows “cluster-type” agglomeration characteristics. However, the development level gap between provinces has remained the same. The southeast coastal economic zone has become an essential high-level development level of innovation ecosystems. (2) The innovation ecosystem has a significant spatial spillover effect on low-carbon transition. This conclusion still holds after multiple robustness tests. (3) In the process of low-carbon transition, the driving effect of the innovation ecosystem shows a “U” shaped stage characteristic of first decreasing and then increasing. (4) The impact of the innovation ecosystem on low-carbon transition varies within different economic circles. Spatial spillover has a boundary effect and the spillover peaks at 1200 km. This study provides theoretical support and empirical evidence based on China’s situation for transforming and developing a low-carbon economy. It provides important policy implications for accelerating low-carbon technological innovation, promoting sustainable development, and responding to climate change.